Education towards Equality: A Review of the Contribution of Distance Learning Technology in Expanding Access and Promoting Social Equality - Priyanto, Dwi (PT. LITERASI SAINS NUSANTARA, 2024)
Education stands as one of the primary pillars in nation-building. However, in many countries, disparities in access and quality of education remain significant issues that hinder the achievement of social equality. This research aims to delve deeply into the contribution of distance learning technology in expanding educational access and promoting social equality. The research method employed is a qualitative literature review drawing data from Google Scholar spanning from 2012 to 2024. The qualitative approach was chosen to allow the researcher to gain a profound and contextual understanding of the topic under study. The study findings indicate that distance learning technology holds significant potential in transforming the educational landscape towards social equality. Through online platforms, educational access can be extended to remote areas and to individuals who may not have had the opportunity to access quality education previously. The flexibility of learning time also emerges as one of the advantages of this technology, allowing individuals to tailor their study schedules according to their needs.